Triad of Supply Chain Orientation, Strategies and Competencies in Construction Industry - Mubarak, Muhammad Faraz; Ali Shaikh, Fazal; Sohu, Samiullah (International Journal of Sustainable Construction Engineering and Technology, 2019)
Construction sector is considered as the pillar of Pakistan’s economic development. Numerous researchers have emphasized the role of supply chain orientation and supply chain strategies to uplift the sustainability within supply chains of construction industries. However, the lack of studies focused on the impact on supply chain orientation in Pakistan. Hence, this article examines the impact of supply chain orientation, supply chain competence and supply chain strategy of the Pakistani construction sector. The study adopted the non-probability sampling approach and 183 questionnaires survey data is collected from 75 construction firms in Sindh. The study is applied Partial Least Square-Structural Equation Modelling technique to analyze the collected data. The findings of the study revealed that all the relationships are positive and significant. The supply chain orientation (SCO) with supply chain strategy (SCS) with p<0.000, Î²=0.11, supply chain orientation (SCO) and supply chain competence (SCC) with p<0.000, Î²=0.34, SCO having a positive significant effect on SCC with p<0.000, Î²=0.22, SCS is playing a mediating role between SCO and SCC. It means that SCO improves SCS as a result p<0.000, Î²=0.15 and the relationship of SCS further improves SCC with p<0.000, Î²=0.11. The result shows that SCO is an important and significant tool in order to increase SCS and SCC. Hence, this study can help to device certain policies to cope up the issues that are the reasons for declining the construction performance